2017
DOI: 10.1161/strokeaha.117.017080
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Thromboinflammation by Hyperglycemia Precipitates Cerebral Infarct Growth and Hemorrhagic Transformation

Abstract: A cute ischemic stroke (AIS) remains a leading cause of disability, cognitive impairment, and mortality worldwide, despite the development of revascularization therapies. Besides recanalization status, other prognostic factors in AIS patients are associated with clinical outcome. Among them, hyperglycemia has been found to be associated with hemorrhagic transformation (HT) and worsened neurological outcomes. 1,2 Given that 40% to 50% of AIS patients present with hyperglycemia, 3 understanding and reducing hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 35 publications
9
76
1
Order By: Relevance
“…In agreement with an earlier study by del Zoppo and Mabuchi, we showed recently that neutrophils represented the vast majority of leukocytes being recruited to the ischemic hemisphere microvasculature during AIS . A previous study using intravital microscopy to investigate leukocyte–endothelium interactions also reported that neutrophil recruitment to the ischemic brain was predominant in the venous compartment .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with an earlier study by del Zoppo and Mabuchi, we showed recently that neutrophils represented the vast majority of leukocytes being recruited to the ischemic hemisphere microvasculature during AIS . A previous study using intravital microscopy to investigate leukocyte–endothelium interactions also reported that neutrophil recruitment to the ischemic brain was predominant in the venous compartment .…”
Section: Discussionsupporting
confidence: 93%
“…In fact, we showed in this study that BBB disruption originates from sites of neutrophil recruitment. As reported previously, hemorrhagic transformation in the form of petechiae is promoted by hyperglycemia, which primes neutrophils for activation and interactions with endothelial cells . In the same study, hemorrhagic transformation originated from areas showing persistent hypoperfusion in magnetic resonance imaging despite recanalization.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations